Experimental investigation on the performance of earth-air pipe heat exchanger for different soil compaction levels. (September 2017) - Elminshawy, Nabil A.S.; Siddiqui, Farooq R.; Farooq, Qazi U.; Addas, Mohammad F.
Highlights: A significant induced air temperature drop up to 21 °C is achieved. The cooling capacity is increased up to 76% for the studied range of flow rate. The cooling capacity is increased up to 227% for the studied range of Ta, i . The cooling capacity is dropped up to 84% for rise in Ts, in from 20 to 30 °C. Maximum effectiveness up to 0.7 is achieved at soil initial temperature 25 °C. Abstract: In this paper, a new design of atmospheric air passive cooling system which consists of an earth-air pipe heat exchanger is proposed. The objective of this system is to cool the warm ambient air for thermal applications in hot arid areas. A 1.5 m long copper pipe with 1.5 cm inner diameter was buried under the soil contained in a galvanized steel drum. The blower and air heater were used at pipe inlet to induce warm air inside the pipe which gets cooled in earth-air pipe heat exchanger. The experiments were performed under the controlled conditions of operating parameters such as induced air temperature, flow rate and soil bulk temperature. The performance of considered heat exchanger was studied for three different soil compaction levels with distinct values of relative density, void ratio and porosity. The results showed that induced air temperature was dropped in the range between 8 and 24 °C across the earth-air pipe heat exchanger and the system effectiveness varied between 0.3 and 0.7 depending on the operating conditions and soil compaction.